An age-related reduction of brain TBPH/TDP-43 levels precedes the onset of locomotion defects in a Drosophila ALS model. (17th December 2015) - Cragnaz, L.; Klima, R.; De Conti, L.; Romano, G.; Feiguin, F.; Buratti, E.; Baralle, M.; Baralle, F.E.
Highlights: TDP-43 levels decrease physiologically during aging in Drosophila and mice. The reduction is seen at protein and mRNA level in the brain. Aggregation does not hamper normal development and early adult life. TBPH reduction combined with the presence of aggregates triggers a locomotive defect. A similar pathway may be active in the pathogenesis of human ALS. Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease. The average age of onset of both sporadic and familial cases is 50–60 years of age. The presence of cytoplasmic inclusions of the RNA-binding protein TAR DNA-binding protein-43 (TDP-43) in the affected neurons is seen in 95% of the ALS cases, which results in TDP-43 nuclear clearance and loss of function. The Drosophila melanogaster ortholog of TDP-43 (TBPH) shares many characteristics with the human protein. Using a TDP-43 aggregation inducer previously developed in human cells, we created a transgenic fly that shows an adult locomotive defect. Phenotype onset correlates with a physiologically age-related drop of TDP-43/TBPH mRNA and protein levels, seen both in mice and flies. Artificial reduction of mRNA levels, in vivo, anticipates the locomotion defect to the larval stage. Our study links, for the first time, aggregation and the age-related, evolutionary conserved reduction of TDP-43/TBPH levels with the onset of an ALS-like locomotion defect in a Drosophila model. A similar process might trigger the human disease.